Understanding the Potential of Bio-Carbon Capture and Storage from Biomass Power Plant in Indonesia - Zefania Praventia Sutrisno; Attaya Artemis Meiritza; Anggit Raksajati (Purnomo Yusgiantoro Center, 2021)
Indonesia is currently experiencing a significant increase in population, industrialization and energy demand. As the energy demand increases, so does the production of climate-altering CO2 emission. Biomass power plants have emerged as a low carbon power generation alternative, utilizing agricultural and industrial waste. Biomass power plants have the potential of being a carbon-negative power generation technology in the near future by integrating carbon and capture storage (bio-CCS). The objective of this paper is to analyze and map potential CO2 emission in the processes of biomass power plants from gasification and firing or co-firing technology, then recommend suitable carbon capture technology based on the biomass power plant characteristics in Indonesia. The CO2 emission to be captured in the gasification process is 11-15% of the producer gas, while in co-firing it is 7-24% of the flue gas stream. Using biomass instead of coal in power plants reduces the electric efficiency and increases the plant’s in-house emission, but when analyzed in a wider boundary system it is apparent that the net GWP and CO2 emission of biomass power plants are way smaller than coal power plant, moreover when equipped with carbon capture unit. Biomass power plant that uses firing technology can reduce CO2 emission by 148% compared to typical coal power plant. Installing carbon capture unit in biomass firing power plants can further reduce the specific CO2 emission by 262%. If carbon capture technology is implemented to all existing biomass power plants in Indonesia, it could reduce the greenhouse gas emission up to 2.2 million tonnes CO2 equivalent annually. It is found that there are 3 significant designs for gasification technology: NREL design, Rhodes & Keith design and IGBCC+DeCO2 design. The first two designs are not suitable to be retrofitted into existing biomass power plants in Indonesia since they are based on a specific BCL/FERCO gasifier. While IGBCC+DeCO2 design still needs further study regarding its feasibility. While for firing, the most promising technology to be applied in the near future is solvent-based absorption because it is already on commercial scale for coal-based power plants and can be implemented for other source, e.g. biomass power plant. Bio-CCS in existing biomass power plant with firing technology is likely to be implemented in the near future compared to the gasification, because it applies the post combustion capture as an “end-of-pipe” technology which is generally seen as a more viable option to be retrofitted to existing power plants, resulting in potentially less expensive transition.